PENINGKATAN PEMAHAMAN INFORMASI LAPORAN KEUANGAN BERDASARKAN SAK EMKM - Lulu Amalia Nusron; Anandita Zulia Putri; Ningrum Pramudiati; Zidni Husnia Fachrunnisa; Yennisa (POLITEKNIK LP3I JAKARTA, 2024)
There are many MSME business actors and they are spread across urban, rural, and even remote areas. MSME businesses do not require a high level of education so that Indonesian people with low levels of education can also become actors in this business. Due to the lack of knowledge and understanding of accounting and business financial reports, the purpose of this activity is to increase understanding of the importance of recording and preparing financial reports in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). This activity was carried out using the method of socialization and mentoring of one of the MSME actors in Yogyakarta, namely Meyva Collection. Previously, business actors still used private in their business results, did not separate personal and business transaction accounts, and did not record consignment sales. The results of this community service activity are expected to increase the knowledge of Meyva Collection business actors by routinely recording expenses such as sewing wages, purchasing raw materials for fabrics, determining the cost of production, so that they can make financial statements of profit and loss. In addition, we also hope that Meyva Collection business actors will routinely record direct sales and consignment income in accordance with SAK EMKM. This activity can foster a mindset in business actors that understanding financial report information based on SAK EMKM is very important for business development and capital participation.